Improved response using coopetitive structures: System dynamics lessons for horticulture supply chains - Wood, Lincoln (Science Technology Press, 2011)
Working in clusters companies must balance competitive and cooperative pressures as they grapple with the state of 'coopetition'. Benifits from cooperating in this manner include sharing and gaining access to new resources and improving information sharing and stock positions for the supply chain, improve service levels to customers. Through the examination of a horticulture supply chain from New Zealand, a supply chain model is developed using a system synamics approach (a stock and flow diagram). This is used to demonstrate some of the key managerial levers or influence points that the coopetitive structure have used to improve their performance in the marketplace to boost their competitiveness, focusing on improved response and flow in the supply chain. Lessons are drawn from this to build a more complete simulation model in the future.